Equivalent circuit properties of organic food extracts doped hydrogels and their applications in bioelectronics - Okutan, M.; Coskun, R.; Ozturk, M.; Yalcin, O.; Toker, C. (ELSEVIER, 2021)
Dielectric/electrical properties of organic food extracts doped hydrogels, which can be envisaged to lead the technology applications of biosensors, bio-imaging and wireless biological sensing schemes in bioelectronic circuits, were analysed at room temperature by means of impedance spectroscopy. Electrode and interfacial polarization mechanisms were determined to be dominant on the dielectric properties of pure and organic food extracts doped hydrogels in the low frequency region. Dielectric relaxation, viscoelastic mechanism, Brownian motion of food extract molecules and Maxwell-Wagner approach were used to explain the dielectric properties of the samples in the high frequency region. It was determined that the dielectric plane plots that provide information about the transmission mechanism of all samples are compatible with the Cole-Cole relaxation models. The conductivity characteristics of the all samples depending on the s parameter/power law exponent were explained for the three different regions by dc conductivity, the Correlated Barrier Hoping conductivity and Quantum Mechanical Tunnel conductivity models, respectively. From the experimental results obtained in this study, it was concluded that organic food extracts doped hydrogels are an inspirational material for applications such as biosensors, bio imaging and wireless bio-sensing device that can be used in bio-systems. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Hydrogels; Organic foods; Dielectric properties; Organic conductivity; Bioelectronics; DIELECTRIC-PROPERTIES; SYNTHETIC CIRCUITS; BROWNIAN-MOTION; LIQUID; SPECTROSCOPY; ABSORPTION; DISPERSION; NETWORKS; SINGLE; TIME; Chemistry; Physics